Tourism and Travel During the Cold War Negotiating Tourist Experiences Across the Iron Curtain - Bechmann Pedersen, Sune 1982- (Routledge Studies in the History of Russia and Eastern Europe Ser., 2019)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- List of illustrations -- List of abbreviations -- Notes on contributors -- Acknowledgements -- Crossing the Iron Curtain: an introduction -- Part I Organising Western tourism in the East -- 1 Exporting holidays: Bulgarian tourism in the Scandinavian market in the 1960s and 1970s -- 2 The lure of capitalism: foreign tourists and the shadow economy in Romania, 1960-1989 -- 3 Experiencing communism, bolstering capitalism: guided bus tours of 1970s East Berlin -- Part II Encounters -- 4 The Artek camp for Young Pioneers and the many faces of socialist internationalism -- 5 Foreign tourists, domestic encounters: human rights travel to Soviet Jewish homes -- 6 "Much more freedom of thought than expected there": Rosey E. Pool, a Dutch fellow traveller on holiday in the Soviet Union (1965) -- 7 The Stalinist utopia of the Adriatic: Swedish tourists in communist Albania -- Part III The politics of tourism during the Cold War -- 8 Playing the tourism card: Yugoslavia, advertising, and the Euro-Atlantic tourism network in the early Cold War -- 9 Making Iron Curtain overflights legal: Soviet-Scandinavian aviation negotiations in the early Cold War -- 10 Concluding remarks: tourism across a porous curtain -- Index.